Implementasi Qr Code Pada Peminjaman Buku Perpustakaan Sekolah Berbasis Mobile - Anjas Saputra; Muhammad Fauzan Azima (Politeknik Negeri Sriwijaya, 2023)
The library is an important part of the school. At SMK YADIKA NATAR, South Lampung, all library administration data processing processes do not yet have a good management information system. This causes the process of borrowing books to take time because librarians have to record data on students who borrow books. In addition, when students want to borrow books at the library, the membership card is held as collateral and students will be given paper as a description of the deadline for borrowing the book. This study aims to design an Android-based software that makes it easier for librarians to manage borrowing and returning books at the library and to make it easy for students to borrow the books they need. The software development method in this study uses the Rapid Application Development (RAD) method and the algorithm used to build this Android-based software is the base64 algorithm. The results of the application can make it easier to use in borrowing books in the school library using a qr code. In addition, the software built can be utilized by the school to make it easier to borrow books at the school library. This software is capable of running on the Android operating system with a minimum version of 6.0.